Continued warming, salinification and oxygenation of the Greenland Sea gyre. Issue 1 (1st January 2018) - Lauvset, Siv K.; Brakstad, Ailin; Våge, Kjetil; Olsen, Are; Jeansson, Emil; Mork, Kjell Arne
Abstract: The Greenland Sea gyre is one of the few areas where the water column is ventilated through open ocean convection. This process brings both anthropogenic carbon and oxygen from the atmosphere and surface ocean into the deep ocean, and also makes the Greenland Sea gyre interesting in a global perspective. In this study, a combination of ship- and float-based observations during the period 1986–2016 are analysed. Previous studies have shown warming and salinification of the upper 2000 m until 2011. The extended data record used here shows that this is continuing until 2016. In addition, oxygen concentrations are increasing over the entire period. The changes in temperature, salinity, and especially oxygen have been more pronounced since the turn of the century. This period has also been characterised by deeper wintertime mixed-layer depths, linking the warming, salinification and oxygenation to strengthened ventilation in the Greenland Sea gyre after 2000. The results also demonstrate that the strengthened ventilation can be tied to advection of warmer and more saline surface water from the North Atlantic through the Faroe-Shetland Channel. This advection has led to more saline surface waters in the Greenland Sea gyre, which is contributing to the deeper wintertime mixed layers.